Listeria monocytogenes Meningitis in an Immunosuppressed Patient with Autoimmune Hepatitis and IgG4 Subclass Deficiency - Shahin Gaini (Case Reports in Infectious Diseases)
A 51-year-old Caucasian woman with Listeria monocytogenes meningitis was treated and discharged after an uncomplicated course. Her medical history included immunosuppressive treatment with prednisolone and azathioprine for autoimmune hepatitis. A diagnostic work-up after the meningitis episode revealed that she had low levels of the IgG4 subclass. To our knowledge, this is the first case report describing a possible association between autoimmune hepatitis and the occurrence of Listeria monocytogenes meningitis, describing a possible association between Listeria monocytogenes meningitis and deficiency of the IgG4 subclass and finally describing a possible association between Listeria monocytogenes meningitis and immunosuppressive therapy with prednisolone and azathioprine.